2021
DOI: 10.1080/14413523.2021.1880767
|View full text |Cite
|
Sign up to set email alerts
|

Identified, but not identical: exploring the influence of collective narcissism in team identification

Abstract: To date, inquiry into team identification has focussed on the implications for consumer behaviour, with relatively limited focus on within group differences of highly identified fans. In the current study, collective narcissism is used to explore attitudinal and behavioural differences among highly identified fans. By interviewing highly identified fans both high and low in collective narcissism, we explore the unique attributes of highly narcissistic fans and how these differ from low narcissistic fans who ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 44 publications
2
13
0
1
Order By: Relevance
“…Moreover, the absence of a significant direct effect of team ID on OT underscores the importance of identifying other factors that determine the conditional influence of team ID. Our findings clarify the underlying process of OT and contribute to the literature on the relationship between team ID and dysfunctional fandom (Larkin & Fink, 2019;Larkin et al, 2021;Toder-Alon et al, 2019). Another important addition of our work to the extent literature is to join recent research in recognizing and examining individual differences among a group of identified fans as we found empirical evidence for the theoretical link between CN, team ID, and OP (Larkin et al, 2021(Larkin et al, , 2022.…”
Section: Theoretical Implicationssupporting
confidence: 66%
See 3 more Smart Citations
“…Moreover, the absence of a significant direct effect of team ID on OT underscores the importance of identifying other factors that determine the conditional influence of team ID. Our findings clarify the underlying process of OT and contribute to the literature on the relationship between team ID and dysfunctional fandom (Larkin & Fink, 2019;Larkin et al, 2021;Toder-Alon et al, 2019). Another important addition of our work to the extent literature is to join recent research in recognizing and examining individual differences among a group of identified fans as we found empirical evidence for the theoretical link between CN, team ID, and OP (Larkin et al, 2021(Larkin et al, , 2022.…”
Section: Theoretical Implicationssupporting
confidence: 66%
“…Fans with high degrees of team ID would also tend to engage in favorable consumption behaviors, reflected in game attendance, merchandise purchase, and preference for team sponsors’ products and services (e.g., Carlson & Donavan, 2013; Fink et al, 2002; James et al, 2019; Jang et al, 2018). Despite extensive literature on positive attachments and desirable behaviors associated with team ID, there has been limited research on the negative aspects of team ID with notable exceptions (e.g., Delia, 2017; Doyle et al, 2017; Larkin & Fink, 2019; Larkin et al, 2021; Wakefield & Wann, 2006). While some researchers have argued that team ID is positively related to fan aggression and dysfunctional fandom, others have not found significant relationships or discovered that team ID can mitigate fan aggression (e.g., Larkin & Fink, 2019; Wann et al, 2003).…”
Section: Review Of Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…Collective narcissism of sport fans could also play a role in explaining conspiracy beliefs in the sport context. Collective narcissism (i.e., a defensive identification rooted in a perceived lack of recognition; Golec de Zavala et al, 2009;Larkin et al, 2021) is a robust predictor of conspiracy beliefs according to empirical (Bertin et al, 2022a(Bertin et al, , 2022bCichocka et al, 2016;Marchlewska et al, 2019;Sternisko et al, 2021), and meta-analytic evidence (Biddlestone et al, 2022). The relationship between collective narcissism and conspiracy beliefs blaming external factors for a situation threatening the ingroup image has been proposed to be mediated by the endorsement of a victim status (Bertin & Delouvée, 2021).…”
Section: Racialmentioning
confidence: 99%